Let's Get Engaged! Crossing the Threshold of Marketing’s Engagement Era Proceedings of the 2014 Academy of Marketing Science (AMS) Annual Conference - Obal, Michael W.; Krey, Nina; Bushardt, Christian (Developments in Marketing Science: Proceedings of the Academy of Marketing Science, 2016)
XXV, 896 p. 11 illus., 5 illus. in color.